Pengaruh Modal Intelektual dan Kepuasan Kerja terhadap Kinerja Pegawai Pemerintah Daerah Malang Raya - Sodik, Sodik; Azzuhri, Misbahuddin (Jurnal Aplikasi Manajemen, 2011)
The aims of this research are to find a description of intellectual capital, job satisfaction, and employees performance; and tested explanation about the influence of intellectual capital that include competency, organization commitment, and job control on job satisfaction and performance; job satisfaction on performance; and intellectual capital on performance with job satisfaction as the mediation. The Local Government Officials at some Regencies in East Java which are dispersed in eight regencies, namely: Malang, Malang City, and Batu which were the observation objects and in the implementation this research used the verification research and survey method, with Stratified Random Sampling technique. The data collected by interview and questionnaire as the research technique. The result of descriptive analysis shows that (1) the officials' intellectual capital which observed both of total and each components resulted in moderate high category, (2) officials job satisfaction were observed both of total and each dimensions resulted in high category, expect job satisfaction on the dimensions of pay and promotion still in moderate high category and (3) officials performance were observed both of total and each dimensions resulted in moderate high category, expect performance on dimension of cooperation was in high category. The result of path analysis shows that (1) intellectual capital that include competency, organization commitment, and job control have positive and significant influence on job satisfaction and performance, (2) job satisfaction has positive and significant influence on performance and (3) intellectual capital has positive and significant influence on the performance with job satisfaction as the mediation.